Properties governing the flow of solution and air through crushed ore for heap leaching - Robertson, Stefan (Department of Chemical Engineering, 2025)
Heap leaching is used extensively for the processing of low-grade copper and gold ores. Heap leaching of low-grade ores is often restricted by the hydrology of the bed, which limits the rate of dissolution of the target mineral. If the ore has low permeability, it may lead to underperformance or even project failure. Although much research has been published on the flow of solution and air through sand, little has been published on the hydrology of coarser rocks. Physical and hydraulic testing of rocks and agglomerates is often incorporated as a part of heap leach design, however, much still relies on experiential rules. Over the past decade, the author has performed physical and hydraulic testing of a large number of ore samples considered for heap leaching. The tests included uni-axial compression tests, hydrodynamic column tests and leach column tests. The data were reviewed to develop relationships between the hydrology and the physical properties of the ore. Compressibility of the agglomerates under load was found to increase with silt + clay (-75 μm) content as high contents of silt and clay result in the destruction of porosity under load. The residual moisture held up in the bed after draining under gravity was found to be proportional to the surface area calculated from the PSD, assuming the bed is a collection of spheres. The residual moisture was also proportional to the sand content (-4.75 mm), as a result of the domination of capillary forces over gravity forces at lower particle diameters and smaller interstitial spaces. The pressure drop versus flow relationship during saturated flow was modelled with a modified form of the Carman-Kozeny equation, whereby the particle radius is replaced with a hydraulic radius. The ratio between the experimentally determined hydraulic radius and the hydraulic radius calculated from the PSD surface area was used to calculate the tortuosity. Since the minimum particle size of the PSD is not exactly known, minimum diameters of 0.002 mm, 0.02 mm and 0.2 mm were used to calculate the PSD surface area. A value of 0.2 mm was found to provide the most physically realistic tortuosity values of between 1.48 and 4.44.